INFORMATION ASYMMETRY AND COST OF CAPITAL: THE MODERATING EFFECT OF INSTITUTIONAL OWNERSHIP - Poniman, Poniman; Erni Husein, Alice; Purba, Neni Marlina Br (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
High information asymmetry will raise suspicions that the company has a high inherent risk, which can reduce the company's value and make it unattractive as an investment asset. Companies with high information asymmetry can affect the increase in the cost of capital. This is because the company needs to offer a high return (cost of capital) so that investors are willing to invest their capital in the company. This study was conducted by testing the effect of information asymmetry on the cost of capital. In addition, this study also tested the moderating role of institutional ownership in strengthening the effect of information asymmetry on the cost of capital. The results of the study prove that information asymmetry has no effect on the cost of capital. The presence of institutional ownership is also known to be unable to strengthen the effect of information asymmetry on the cost of capital. This study contributes to agency theory which highlights the conflict that occurs between shareholders and company management related to information asymmetry.